MEDIA EDUCATION AND ITS PLACE IN UZBEKISTAN (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
The article discusses the generally accepted directions of media education and the media competencies of modern man; the classification of media education; the main variables on which the success of the media education process depends, as well as the social layers on which modern media education is directed. In connection with the increased influence of the media, there is a need to expand the social groups in which media education should be directed.